Phlebological insole: Can it help in the lymphoedema treatment? A scoping review. (June 2023) - De Michele, Manuela; Mastrullo, Monica; Melotto, Gianluca; Tedeschi, Roberto
Background: The treatment of lymphoedema requires a multi-professional and interdisciplinary approach. Despite being prescribed in the management of lymphatic disorders, the effectiveness of the phlebological insoles is still under investigation. Aim: This scoping review aims to identify and analyse evidence regarding the efficacy of phlebological insoles as a conservative intervention for lower limb lymphoedema. Method: The following databases were searched up to November 2022: PubMed, Cochrane Library, CINAHL Complete, PEDro and Scopus. Preventive and conservative interventions were considered. Studies considering people with lower limb oedema, of any age and type of oedema, were eligible for inclusion. No restrictions in terms of language, year of publication, study design and type of publication were applied. Additional studies were sought through grey literature. Results: From 117 initial records, 3 studies met the inclusion criteria. Two quasi-experimental studies and one randomised cross-over study were included. The results of the examined studies confirmed the positive effects of insoles usage and foot and ankle mobility on the venous return. Conclusion: This scoping review provided an overview of the topic. The studies analysed in this scoping review have shown that insoles seem to be beneficial in reducing the lower limb oedema in healthy individuals. However, there are still no comprehensive trials confirming this evidence on people with lymphoedema. The small number of identified articles, the selection of participants not affected by lymphoedema, the use of heterogeneous devices in terms of modifications and materials highlight the need of further investigations. Future trails should include people affected by lymphoedema, address the choice of materials in manufacturing the insoles and take in consideration the patients' adherence to the device and concordance to the treatment.